Safety and immunogenicity of a tetravalent dengue vaccine in children aged 2–17 years: a randomised, placebo-controlled, phase 2 trial. Issue 10234 (2nd May 2020) - Tricou, Vianney; Sáez-Llorens, Xavier; Yu, Delia; Rivera, Luis; Jimeno, José; Villarreal, Ana Cecilia; Dato, Epiphany; Saldaña de Suman, Onix; Montenegro, Nathali; DeAntonio, Rodrigo; Mazara, Sonia; Vargas, Maria; et al.
Summary: Background: An unmet clinical need remains for an effective tetravalent dengue vaccine suitable for all age groups, regardless of serostatus. We assessed the immunogenicity and safety of three different dose schedules of a tetravalent dengue vaccine (TAK-003) over a 48-month period in children living in dengue-endemic countries. Methods: We did a large, phase 2, double-blind, placebo-controlled trial at three sites in the Dominican Republic, Panama, and the Philippines. Healthy participants aged 2–17 years were randomly assigned 1:2:5:1 using an interactive web response system with stratification by age to receive either a two-dose primary series (days 1 and 91), one primary dose (day 1), one primary dose plus booster (days 1 and 365), or placebo. Participants and relevant study personnel were masked to the random assignment until completion of the study at month 48. To maintain masking, TAK-003 recipients were administered placebo doses when appropriate. The primary objective was assessment of neutralising geometric mean titres for each serotype to month 48 assessed in the per-protocol immunogenicity subset. Secondary safety endpoints included proportions of participants with serious adverse events and symptomatic virologically confirmed dengue. This study is registered with ClinicalTrials.gov, NCT02302066 . Findings: Between Dec 5, 2014, and Feb 13, 2015, 1800 children were randomly assigned to the following groups: two-dose primary series (n=201), one primary dose (n=398), one primary dose plus 1-year booster (n=1002), and placebo (n=199). Of them, 1479 (82%) participants completed the 48-month study. Immunogenicity endpoints were assessed in 562 participants enrolled in the immunogenicity subset, of whom 509 were included in the per-protocol subset. At month 48, antibody titres remained elevated in all TAK-003 groups compared with placebo, irrespective of baseline serostatus. At month 48, geometric mean titres were 378 (95% CI 226–632) in two-dose, 421 (285–622) in one-dose, 719 (538–960) in one-dose plus 1-year booster, and 100 (50–201) in placebo recipients against DENV 1; 1052 (732–1511), 1319 (970–1794), 1200 (927–1553), and 208 (99–437) against DENV 2; 183 (113–298), 201 (135–298), 288 (211–392), and 71 (37–139) against DENV 3; and 152 (97–239), 164 (114–236), 219 (165–290), and 46 (26–82) against DENV 4; and tetravalent seropositivity rate was 89% (79–96), 86% (80–92), 97% (93–99), and 60% (47–72), respectively. Virologically confirmed dengue was recorded in 37 (2%) TAK-003 and 13 (7%) placebo participants, with a relative risk of 0·35 (0·19–0·65). No vaccine-related serious adverse events or severe dengue virus disease were reported. Interpretation: TAK-003 elicited antibody responses against all four serotypes, which persisted to 48 months post-vaccination, regardless of baseline serostatus. No important safety risks were identified. We observed a long-term reduction in risk of symptomatic dengue virus disease in vaccinees. Results from this study provide a long-term safety database and support assessment of the vaccine in the ongoing phase 3 efficacy study. Funding: Takeda Vaccines.